THE EXISTENCE OF CRIMINAL LAW IN NATIONAL CRIMINAL LAW REFORM - Abdul Kholiq; Zabidin Zabidin; Pratiwi Ayu Sri Daulat (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Darma Agung, 2023)
The problem of reforming criminal law is one of the impo important issues that need in all its aspects in connection with efforts to reform criminal law in our country. It is said to be important and even the most important because legal experts often interpret criminal law as a double-edged sword. On the one hand, it is a law to protect society from the threat of crime, but on the other hand, there are times, there are times when human rights temporarily or permanently deprive a person of liberty. Criminal law reform has existed since 1946 with the issuance of Law Number 1 of 1946 concerning criminal law regulations. Criminal law reform as part of criminal politics is in place, and it is time to implement it. This is mainly related to the provisions of the old criminal law, which are regulated in the criminal law code as an